101 LIPOPROTEIN ASSOCIATED PHOSPHOLIPASE A2 IN STEMI VS NSTE-ACS PATIENTS: A MARKER OF CARDIOVASCULAR ATHEROSCLEROTIC RISK RATHER THAN THROMBOSIS. (15th December 2022) - Verdoia, Monica; Gioscia, Rocco; Rognoni, Andrea; Luca, Giuseppe De
Abstract: Background: The precise role of Lipoprotein associated phospholipase A2 (Lp-PlA2) in the pathogenesis of acute coronary syndromes (ACS) and in the prediction of future cardiovascular events is still debated. So far, few data exist on the variations of Lp-PlA2 activity in ACS and especially in NSTE-ACS vs STEMI patients, where thrombotic and atherosclerotic mechanisms could play a differential role. The aim of the present study was, then, to compare Lp-PlA2 activity according to the type of ACS presentation. Methods: A consecutive cohort of patients undergoing coronary angiography for acute coronary syndrome (ACS) were included and divided according to presentation for non ST-segment elevation-ACS or ST-segment elevation Myocardial Infarction (STEMI). Lp-PLA2 activity was assessed on blood samples drawn at admission using the Diazyme Lp-PlA2 Activity Assay. Results: We included in our study 117 patients, of whom 31 (26.5%) presented with STEMI. STEMI patients were significantly younger (p=0.05), displayed a lower rate of hypertension (p=0.002), previous MI (p=0.001) and PCI (p=0.01) and used less frequently statins (p=0.01) and clopidogrel (p=0.02). White blood cells and admission glycemia were increased in STEMI (p=0.001, respectively). The prevalence and severity of CAD was not different according to ACS types, but for a higher prevalence of thrombus (p<0.001) and lower TIMI flow (p=0.002) in STEMI. The levels of Lp-PlA2 were significantly lower in STEMI as compared to NSTE-ACS patients, (132±41.1 vs 154.6 ±40.9 nmol/min/mL, p=0.01). In fact, the rate of patients with Lp-PlA2 above the median (148 nmol/min/mL) was significantly lower in STEMI patients as compared to NSTE-ACS (32.3% vs 57%, p=0.02, adjusted OR[95% CI]=0.20[0.06-0.68], p=0.010). Moreover, a direct linear relationship was observed between Lp-PlA2 and LDL-C (r=0.47, p<0.001), but not with inflammatory biomarkers. Conclusion: The present study shows that among ACS patients, the levels of Lp-PlA2 are inversely associated with STEMI presentation and thrombotic coronary occlusion, being instead increased in NSTE-ACS patients, and with recurrent cardiovascular events, therefore potentially representing a marker of a more aggressive atherosclerotic disease and higher cardiovascular burden and risk.